THE INFLUENCE OF THE ARROW PUSHING STRUCTURE ON ITS PERFORMANCE - Gevko , R.B.; Rud , A.V.; Pavelchuk , Yu.F. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The article proposes a working body of seeders for subsoil-spreading sowing of cereals such as arrow paws with the parameters of the working bodies of the cultivator for pre-sowing cultivation of the soil, which is determined by the same working conditions. Similar studies to identify the optimal design parameters of arrow-shaped working bodies on soils with a moisture content of 29.9-31.0% (average soil hardness 1.41 мPa at a depth of 10-12 cm) were conducted by many scientists. They note the shortcomings of the small angle of elevation of the chest paws (grinding) on moist soils, as there is unsatisfactory pruning of the soil layer and breaking it with a rack, which does not provide quality grinding and promotes the formation of ridges. As a result, the traction resistance and the quality of processing, the optimal value of the grinding angle should be within 15 ... 18 °. The decrease in specific traction resistance in accordance with the increase in the width of the working body is explained by the significant share of resistance that falls on the riser of the working body - up to 45%.